Improving global digital elevation models using space-borne GEDI and ICESat-2 LiDAR altimetry data - Narin, Omer Gokberk; Abdikan, Saygin; Gullu, Mevlut; Lindenbergh, Roderik; Sanli, Fusun Balik; Yilmaz, Ibrahim (TAYLOR & FRANCIS LTD, 2024)
Open source Global Digital Elevation Models (GDEMs) serve as an important base for studies in geosciences. However, these models contain vertical errors due to various reasons. In this study, data from two Satellite LiDAR altimetry systems, GEDI and ICESat-2, were used to improve the vertical accuracy of GDEMs. Three different machine learning methods, namely an Artificial Neural Network (ANN), Extreme Gradient Boosting (XGBoost), and a Convolutional Neural Network (CNN), were employed to improve existing DEM data with satellite LiDAR data. The methodology was tested in five areas with varying characteristics. Ground control data were selected from high accuracy DEMs generated from Airborne LiDAR and GNSS data. The use of ANN method improved the vertical accuracy of SRTM data from 6.45 to 3.72 m in Test area-4. Similarly, the CNN method demonstrated an improvement in the vertical accuracy of bare ground SRTM data increasing from 3.4 to 0.6 m in Test area-4. In Test area-5, the ANN method improved the vertical accuracy of SRTM data with slopes between 30 and 60%, increasing from 3.8 to 0.5 m. Notably, the results underscore the successful improvement of GDEMs across all test areas.
Keywords: Global digital elevation models; GEDI; ICESat-2; machine learning; ACCURACY ASSESSMENT; ASTER; FUSION; SRTM; Physical Geography; Remote Sensing